Influence of literacy on abnormal white discharge in women of reproductive age group in a metropolitan city - Kasbe, Abhiram M.; Rajadhyaksha, Nikita G. (International Journal Of Community Medicine And Public Health, 2022)
Background: White vaginal discharge is a physiological process in women, depicting various stages of the menstrual cycle, but when accompanied with an infection of the vagina or cervix, it can present as an abnormal, excessive discharge accompanied with odour, irritation, and a variation in colour. Certain perceptions in women and lack of their knowledge pertaining to genital hygiene play a role on their reproductive health. This study was taken up to find the influence of education (literacy) on the abnormal white discharge. Methods: Total 350 women staying in a slum of a metropolitan city were interviewed for the study. A predesigned semi structured questionnaire was prepared for all the study subjects. Voluntary consent was taken for the study in the language understood by the subjects. Results: The association between literacy (education) and abnormal white discharge was not found to be statistically significant with the p value of 0.819. Conclusions: Literacy was not found to have an influence on the abnormal white discharge in the married women of reproductive age group.